Production process design using Multi-Criteria Analysis - Treitz, Martin (KIT Scientific Publishing, 2006)
Intra- and inter-company production networks have gained increased importance in developed and industrialising countries. By reusing waste of industrial sites as a valuable input within the production network, material cycles can be closed and resource efficiency can be improved.In order to improve the performance of a production process, a detailed mapping of the mass and energy flows is the basis to understand which process characteristics are the main drivers for resource efficiency.The objective of this book is to develop an integrated multi-criteria decision support model for production process design.